Analysis of The Balanced Scorecard Approach For Assessing The Financial and Non-Financial Performance Measurement - Pardede, Tiolina; Pramesworo, Ign. Septo (Indonesian Journal of Business and Entrepreneurship, 2023)
This study aims to analyze the financial and non-financial performance of two gas stations (SPBU) in Jakarta. The analysis of this study uses the Balanced Scorecard approach, which includes four perspectives: finance, customers, internal business processes, and learning growth. The data used in this research includes primary data and secondary data. Primary data is obtained through direct interaction, such as interviews, questionnaires, and direct observation. At the same time, secondary data is obtained by having documents that support the continuity of this research. Questionnaire data processing using the SPSS 24.0 program. The scoring results from the four perspectives amount to 5. It can be concluded that the performance of SPBU X is sufficient. Keywords: balanced scorecard, finance perspective, customer perspective, internal business perspective, learning and growth perspective, performance measurement